Analysis of the hydrogen electrode reaction mechanism in thinlayer cells. 2: Study of hydrogen evolution on microelectrodes by scanning electrochemical microscopy - Bonazza, Horacio (2013)
This work presents an updated equation for analyzing experimental dependences of the tip current (iT) on the tip potential (ET) and the tip-substrate distance (d) by scanning electrochemical microscopy (SECM). The model includes the contribution of a general thin layer cell (TLC) with no aprioristic restrictions about the reaction mechanism. The iT(ET, d) dependence for a particular reaction is governed both by the microelectrode response (at large d values) and by the TLC response (more important at small d values) that result from solving the particular reaction mechanism. This equation was applied for studying the mechanism and for quantifying the elementary kinetic parameters of the hydrogen evolution reaction (her) on platinum and gold microelectrode tips. A dependence of the TLC current on ET previously developed for the her operating through the Volmer–Heyrovsky–Tafel (VHT) mechanism was included in the model to correlate experimental iT(ET, d) curves measured on these two metals. The transition from the VT to the VH route was clearly detected on both metals under conditions of high mass transport rates.